How Does Long Term Use of Surgical Face Mask Affect the Voice in Normophonic Subjects? - Tunç-Songur, Elif; Gölaç, Hakan; Önen, Çiğdem; Duyar, Tugay Rifat; Yılmaz, Metin; Kemaloğlu, Yusuf Kemal (Journal of voice, 2025)
To assess the effects of the longterm-use of surgical face mask (SFM) on acoustic and auditory-perceptual voice parameters in normophonic subjects without any known risk factor related to voice disorders. Of 73 normophonic subjects who were previously included in a couple of studies before the COVID-19 outbreak, 25 people (18 female and 7 male) who were free of any known risk factor related to voice disorders during the outbreak were re-evaluated to assess the long-term effect of SFM on voice by using acoustic (mean F0, Jitter-local, Shimmer-local, Cepstral Peak Prominence (CPP), Noise to Harmonic Ratio (NHR), maximum phonation time (MPT)) and auditory-perceptual (Consensus Auditory-Perceptual Evaluation of Voice (CAPE-V)) parameters and those data found in SFM period were compared with the previous (preSFM) data. MPT and acoustic data were analyzed by PRAAT software. It was seen that the mean F0 value presented a significant increase, while Jitter-local and Intensity values revealed a significant decrease in females after 2 years pass with SFM use (average 22.52 ± 0.18 months).In males, only a significant decrease in Jitter-local was detected. This study is the first longitudinal investigation on the effects of SFM use on acoustic and auditory-perceptual measures of voice. The data in this study, revealed that long-term use of SFM would not appear to be negatively affecting the acoustic parameters of the voice in normophonic subjects (particularly females) without any related risk factors such as tobacco use, reflux, and etc.